3(3v-2)=4(2v+2)

Simple and best practice solution for 3(3v-2)=4(2v+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3v-2)=4(2v+2) equation:


Simplifying
3(3v + -2) = 4(2v + 2)

Reorder the terms:
3(-2 + 3v) = 4(2v + 2)
(-2 * 3 + 3v * 3) = 4(2v + 2)
(-6 + 9v) = 4(2v + 2)

Reorder the terms:
-6 + 9v = 4(2 + 2v)
-6 + 9v = (2 * 4 + 2v * 4)
-6 + 9v = (8 + 8v)

Solving
-6 + 9v = 8 + 8v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-8v' to each side of the equation.
-6 + 9v + -8v = 8 + 8v + -8v

Combine like terms: 9v + -8v = 1v
-6 + 1v = 8 + 8v + -8v

Combine like terms: 8v + -8v = 0
-6 + 1v = 8 + 0
-6 + 1v = 8

Add '6' to each side of the equation.
-6 + 6 + 1v = 8 + 6

Combine like terms: -6 + 6 = 0
0 + 1v = 8 + 6
1v = 8 + 6

Combine like terms: 8 + 6 = 14
1v = 14

Divide each side by '1'.
v = 14

Simplifying
v = 14

See similar equations:

| 2X+1-4=-2X-34 | | 4z/10+7=8 | | 12x=2x+10x+1 | | 3m-8m=110 | | x/9+3=6 | | 9(1.082x+1)=15 | | z/7+3=6 | | 15x^2-47x-10=0 | | 137-(6x+5)=6(x+9)+x | | 2/3x–6=9 | | 5x-4=x+3*2 | | 5[2-g]=0 | | 14=3m+5 | | 5+6=4+Y | | 10[1-2y]=-5[2y-1] | | -3sin(t)+2cos(t)=0 | | 3(3+2x)-4x=59-3x | | 15z-2=(2z+3) | | 3x-(12x-x)=5+2(x-1)-1 | | 3y+5y+2y= | | 6r-6=72-6 | | 5n-30=20 | | 3x-(12-x)=5+2(x+1)-1 | | 5y=11x-7 | | 3(x+5)-2=6x-3(-4+x) | | -8x+3=25 | | 5y=11x+7 | | LNx=-1.6 | | Log(8x-7)/log(x) | | -6f+13=-9z+24 | | 9(5+x)=8(x-4) | | 5+2X=14-4N |

Equations solver categories